Thymidine catabolism promotes NADPH oxidase-derived reactive oxygen species (ROS) signalling in KB and yumoto cells - Sho Tabata (Nature Portfolio, 2018)
Abstract Thymidine phosphorylase (TP) is a rate-limiting enzyme in the thymidine catabolic pathway. TP is identical to platelet-derived endothelial cell growth factor and contributes to tumour angiogenesis. TP induces the generation of reactive oxygen species (ROS) and enhances the expression of oxidative stress-responsive genes, such as interleukin (IL)-8. However, the mechanism underlying ROS induction by TP remains unclear. In the present study, we demonstrated that TP promotes NADPH oxidase-derived ROS signalling in cancer cells. NADPH oxidase inhibition using apocynin or small interfering RNAs (siRNAs) abrogated the induction of IL-8 and ROS in TP-expressing cancer cells. Meanwhile, thymidine catabolism induced by TP increased the levels of NADPH and intermediates of the pentose phosphate pathway (PPP). Both siRNA knockdown of glucose 6-phosphate dehydrogenase (G6PD), a rate-limiting enzyme in PPP, and a G6PD inhibitor, dihydroepiandrosterone, reduced TP-induced ROS production. siRNA downregulation of 2-deoxy-D-ribose 5-phosphate (DR5P) aldolase, which is needed for DR5P to enter glycolysis, also suppressed the induction of NADPH and IL-8 in TP-expressing cells. These results suggested that TP-mediated thymidine catabolism increases the intracellular NADPH level via the PPP, which enhances the production of ROS by NADPH oxidase and activates its downstream signalling.